The effect of maleic anhydride concentration in manufacturing polypropylene grafted maleic anhydride compatibilizer on the test percent of grafting degree - TANJUNG, DENNY AKBAR; JAMARUN, NOVESAR; LUBIS, ROSLIANA (Jurnal Natural, 2024)
The difference in polarity between materials often prevents direct interaction; therefore, a compatibilizer is required to facilitate reactions between polar and non-polar substances. This study aims to investigate the effect of maleic anhydride (MA) concentration on the grafting process of MA onto polypropylene (PP) chains, using benzoyl peroxide (BPO) as an initiator. The blending method employing an internal mixer was used to combine the materials, and the degree of grafting was determined via titration, with three replicates performed for accuracy. The results indicated that the highest grafting degree, 10.28%, was achieved at a composition of 86% PP, 11% MA, and 3% BPO. Fourier Transform Infrared (FTIR) spectroscopy analysis of polypropylene grafted with maleic anhydride (PP-g-MA) revealed new absorption peaks at wavenumbers 1707 cm and 1162 cm. Furthermore, increasing the concentration of maleic anhydride did not significantly affect the grafting degree. This study provides valuable insight for the development of PPg-MA compatibilizers.